EMDR Therapy: Theoretical Foundations, Clinical Effectiveness, and a Comparative Review with Trauma-Focused Cognitive Behavioral Therapy - Deniz Erdoğan; Reşat Güven; Demet Karakartal (Clinical Journal of Health Sciences, 2026)
This study is a systematic review examining the theoretical foundations, historical development, neuropsychological mechanisms, and clinical effectiveness of Eye Movement Desensitization and Reprocessing (EMDR) therapy within the framework of psychiatry, clinical psychology, and trauma literature. Developed by Francine Shapiro in the 1980s, EMDR is a structured and integrative psychotherapy method that combines elements of psychodynamic, cognitive, behavioral, and client-centered approaches and is based on the reprocessing of traumatic memories. The literature search was conducted in line with the PRISMA 2020 guidelines in the PubMed, Web of Science, Scopus, PsycINFO, ULAKBİM TR Index, and Google Scholar databases using the keywords “EMDR,” “eye movement desensitization and reprocessing,” “post-traumatic stress disorder,” and “trauma-focused therapy”; 46 peer-reviewed, full-text studies focusing directly on the method were included. The findings were organized thematically around the Adaptive Information Processing model and the neuropsychological basis of bilateral stimulation, the eight-phase application process, effectiveness in post-traumatic stress disorder (PTSD) as well as depression and anxiety disorders, and comparison with Trauma-Focused Cognitive Behavioral Therapy (TF-CBT). According to the findings, EMDR is similarly effective to TF-CBT in treating PTSD, while it can often achieve results in a shorter time and at a lower cost. In conclusion, EMDR stands out as both an evidence-based and resource-oriented option for treating trauma-related difficulties. However, because the evidence base is at different levels of maturity across domains, findings regarding the distinct contribution of eye movements and effectiveness in non-trauma disorders should be interpreted with caution, and larger, methodologically rigorous randomized controlled trials are needed in these areas. By integrating current meta-analytic evidence within a comparative framework, this review aims to clarify EMDR’s position among evidence-based psychotherapies and to contribute to clinical decision-making. Evaluating international evidence together with the Turkish-language literature further provides a holistic perspective on the method’s local applicability and offers guidance for clinicians and researchers regarding treatment selection and future research priorities, thereby serving as both a theoretical and practical reference.